BUDAYA ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL TANTANGAN PENINGKATAN KINERJA KARYAWAN - Permadi, Indra; Sobar, Agus; Fathussyaadah, Eva; Ginanjar, Noornisa Sarah (2021)
Organizational performance is a manifestation.. of the performance of organizational members. The challenges of improving organizational performance must be addressed with organizational change management and leadership patterns that can boost organizational performance. The research aims to examine the challenges of performance improvement based on organizational cultural factors and the application of transformational leadership. The target population is the employees and leaders of financing companies operating in the Sukabumi region. A total of 97 respondents were obtained using proportional sampling. Analysts use multiple OLS regression. The results of organizational culture research and transformational leadership have a significant effect on improving performance.